Assessing Learner Autonomy and EFL Vocabulary Acquisition: A Case Study - Feng, Teng (Beyond Words, 2015)
The importance of autonomy learning is widely acknowledged in teaching English as a Foreign Language (EFL) in Asian contexts. The present study attempted to report low proficiency level students’ autonomous vocabulary learning. The first part of the present study focused on exploring how learners perceived and experienced their autonomous vocabulary learning, with a questionnaire and group discussion applied to collect data. During the second part of the study, the data were discussed collaboratively by six teachers to identify the different approaches utilized by learners. Priorities included setting weekly goals, self-planning and self-monitoring the process of learning vocabulary. Results also revealed that a weak ‘top-down’ approach in implementing learner autonomy is inadequate. Teachers need to provide scaffolding skills tailored to learners’ context-specific needs, for which a strong ‘bottom-up’ approach is more appropriate in supporting autonomous learning. In this case, classroom time should be allocated to demonstrate the strategies and teachers should work collaboratively to develop resources and materials for learners’ autonomous vocabulary learning. The present study also addressed the need for establishing an effective intervention for supporting learner autonomy. Keywords: learner autonomy, vocabulary learning, self-plan, self-monitor